FINANCIAL POSITIONING OF COMMERCIAL BANKS AND ITS IMPLICATIONS TO BANK MANAGEMENT - Muhamad Muda, (Asian Academy of Management Journal, 1996)
The banking system in Malaysia, like many of the banking systems in the developing countries, emerged to facilitate trade transactions either domestically or cross border and as a tool used by the authority to faster the country's economic growth and development through the process of financial intermediation. While market forces influence the development of individual banks, implementation of government policy will mean introduction of regulatory provisions in the banking system that in turn regulates banks activities and determines banking structure. In addition, changes in the capital formation spurred by the active management of the monetary and fiscal policies, have realigned the supply and demand for capital. A greater emphasis placed into accelerating the growth of the manufacturing and industrial sectors has raised the demand for the longer term funds. At the same time efforts made to manage the interest rate as well as the exchange rates has led to a higher cost of funds, particularly for the longer terms. In view of these developments, banks are expected to reposition their asset-liability structure in order to be in line with the supply and demand for capital. In this paper, we will examine the way banks reposition their assets and liabilities. Implications of these repositioning exercise on the management and profitability is explored.